Artérias da base do encéfalo em suínos (Sus scrofa domesticus - Linnaeus, 1758) da linhagem Camborough 22 - Lima, Eduardo Maurício Mendes de (2002)
The subjects of this study were the arteries of the base of the encephalon in 40 stillborn pigs (Sus scrofa domesticus-Lmnaevrs,, 1758) from the lineage Camborough 22, male and female specimens. The specimens were provided by the creation core of Uberlândia, MG. In ten specimens the cranial arteries were filled with a colored solution of vinyl acetate, followed by a corrosion process in a water-based solution at 25% concentration, of sulfuric acid. In 30 specimens a water-based solution at 50% concentration of colored latex neoprene “450” was injected. Afterwards they were fixed in a water-based solution of formaldehyde at 10% concentration. This process made possible to remark the arteries of the encephalon base surrounding the rostral epidural admirable rete and caudal rete. The rostral epidural admirable rete originate from the internai carotid arteries, maxilary, middle meningeal and externai ophthalmic. However the caudal epidural admirable retes originated from the occipital arteries, condylar and vertebral. The carotid arteries of the encephalon, after emerging into the rostral epidural admirable retes provide rostral and caudal branches. The caudal epidural admirable retes of both sides and also the ventral spinal artery formed the basilar artery, which reached forth dorso-caudally, narrowing its caliber until become an anastomosis through its terminal branches with the caudal branches of the carotid arteries from the encephalon. The arterial course of the encephalon is characterized by rostral and caudal branches of the carotid arteries of the encephalon and also by the left and right terminal branches of the basilar artery. Rostrally was morphologically characterized as an ellipse-like picture, disposed transversally. It presented closed by the rostral communicant arteries. Caudally the arterial course of the encephalon was characterized morphologically by angles among the anastomoses of the caudal branches of the carotid arteries of the encephalon and of the terminal branches of the basilar arteries, as well as the origin of the terminal branches of the basilar artery, its morphological aspect resemble to the caudal half of an hexagon, which presented caudally closed by the terminal emerging branches of the basilar artery. There were no remarkable differences according to the Wilcoxon test the use of the U test by Mann-Whitney.